Distributed computing innovations for business, engineering, and science - Loo, Alfred Wai-Sing, 1951- (Information Science Reference, 2013)
"This book is a collection of widespread research providing relevant theoretical frameworks and research findings on the applications of distributed computing innovations to the business, engineering and science fields"--